On some fixed point theorems for Ćirić operators - Mădălina Moga; Radu Trușcă (Miskolc Mathematical Notes)
In this paper, we will present existence and localization fixed point theorems and stability results for the fixed point problem involving some very general classes of operators (single-valued and multi-valued), namely for Ćirić type operators. Then, an application to homotopy principles is given. Our results complement and extend the works in the literature.